Health-related quality of life and its associated factors among hemophilia patients: experience from Ethiopian Hemophilia Treatment Centre - Sitina Iyar; Girma Tekle Gebremariam; Dessale Abate Beyene; Amha Gebremedhin; Tamrat Assefa Tadesse (Journal of Pharmaceutical Health Care and Sciences, 2024)
Abstract Background Hemophilia is a rare genetic condition that is often overlooked and underdiagnosed, particularly in low-income countries. Long-term spontaneous joint bleeding and soft tissues can have a significant negative impact on a patient’s health-related quality of life (HRQoL). The objective of this study was to assess HRQoL and its associated factors in Ethiopian patients with hemophilia. Methods A cross-sectional survey was conducted among patients with hemophilia at Tikur Anbessa Specialized Hospital (TASH) in Addis Ababa, Ethiopia. Patients were recruited consecutively during follow-up visits. The European Quality of Life Group’s 5-Domain Questionnaires at five levels (EQ-5D-5L) and Euro Quality of Life Group’s Visual Analog Scale (EQ-VAS) instruments were used to assess HRQoL. The EQ-5D-5L utility score was computed using the disutility coefficients. We applied the Krukal-Wallis and Mann–Whitney U tests to determine the differences in EQ-5D-5L and EQ-VAS utility scores between patient groups. A multivariate Tobit regression model was used to identify factors associated with HRQoL. Statistical analyses were performed using STATA version 14 and statistical significance was determined at p < 0.05. Results A total of 105 patients with hemophilia participated in the study, with a mean (standard deviation (SD) age of 21.09 (± 7.37] years. The median (IQR) EQ-5D-5L utility and EQ-VAS scores were 0.86 (0.59–0.91) and 75 (60.0–80.0), respectively. Age was significantly negatively associated with the EQ-5D-5L utility index and EQ-VAS (β = -0.020, 95 CI = -0.034, -0.007) and β = -0.974, 95% CI = -1.72, 0.225), respectively. The duration since hemophilia diagnosis (β-0.011, 95% CI, 0.001–0.023) and living out of Addis Ababa (β = -0.128, 95% CI, -0.248-, -0.007) were also significantly negatively associated with the EQ-5D-5L utility index.. Conclusion The median EQ-5D-5L utility and EQ-VAS scores of patients with hemophilia were 0.86 (0.59–0.91) and 75 (60.0–80.0), respectively. Older age, living far from the Hemophilia Treatment Center (HTC), and longer duration since diagnosis were significantly negatively associated with HRQoL. HRQoL may be improved by providing factor concentrates, decentralizing HTCs in different parts of the country, increasing awareness of bleeding disorders among health professionals, and providing psychosocial support to affected patients.